«“We Are All Mad Here”: Sylvia Plath’s "The Bell Jar" as a Political Novel». - de la Parra Fernández, Laura (Revista de Filología Románica, 2017)
Sylvia Plath’s roman à clef The Bell Jar has largely been read as an autobiographical novel and as the key to understanding her suicide. The novel, however, presents an important political complexity—the contradictions Esther faces in post-WWII, 1950s American society, the unattainable and conflicting ideals of womanhood, and the political treason that betraying them implies, dealt with as madness. Esther Greenwood’s descent into madness is no more than the reflection of the sick, hypocritical society she lives in, and an attempt to escape from her obligations as an American woman. However, the institution of psychiatry was closely related to the politics of the time, and acted as a means of control over the population, especially women, through the use of treatments such as ECT and lobotomy. I would like to look at how Cold War politics, gender, and psychiatry interact in The Bell Jar in order to submit American society to the conformism and consumerism that dominated the 1950s.